PHRASES IN THE DEVELOPMENT OF TOURISM AND TOURIST CULTURE - Saitkhanova Aziza; Jumaboyev Asadbek Axmed o’g’li (International Journal of Economic Integration and Regional Competitiveness, 2024)
This article provides a concise exploration of cultural tourism in Uzbekistan, examining its historical roots and contemporary significance. Through evidence-based insights and recommendations, it offers a roadmap for policymakers and stakeholders to foster sustainable growth while preserving Uzbekistan's cultural heritage. It serves as a valuable resource for understanding and advancing cultural tourism initiatives in the region.